CARMA1- and MyD88-dependent activation of Jun/ATF-type AP-1 complexes is a hallmark of ABC diffuse large B-cell lymphomas - Juilland, Mélanie (Blood, 2016)
A hallmark of the diffuse large B-cell lymphoma (DLBCL) of the activated B-cell (ABC) type, a molecular subtype characterized by adverse outcome, is constitutive activation of the transcription factor nuclear factor–κB (NF-κB), which controls expression of genes promoting cellular survival and proliferation. Much less, however, is known about the role of the transcription factor activator protein-1 (AP-1) in ABC DLBCL. Here, we show that AP-1, like NF-κB, was controlled by constitutive activation of the B-cell receptor signaling component caspase recruitment domain-containing membrane-associated guanylate kinase 1 (CARMA1) and/or the Toll-like receptor signaling component myeloid differentiation primary response gene 88 (MyD88) in ABC DLBCL cell lines. In contrast to germinal center (GC) B-cell (GCB) DLBCL, ABC DLBCL cell lines expressed high levels of the AP-1 family members c-Jun, JunB, and JunD, which formed heterodimeric complexes with the AP-1 family members activating transcription factor (ATF) 2, ATF3, and ATF7. Inhibition of these complexes by a dominant-negative approach led to impaired growth of a majority of ABC DLBCL cell lines. Individual silencing of c-Jun, ATF2, or ATF3 decreased cellular survival and revealed c-Jun/ATF2-dependent control of ATF3 expression. As a consequence, ATF3 expression was much higher in ABC vs GCB DLBCL cell lines. Samples derived from DLBCL patients showed a clear trend toward high and nuclear ATF3 expression in nodal DLBCL of the non-GC or ABC subtype. These findings identify the activation of AP-1 complexes of the Jun/ATF-type as an important element controlling the growth of ABC DLBCL.